Voluntary Versus Involuntary Forms of Employment: Evidence from Poland - Dominika BAK-GRABOWSKA (Communications of International Proceedings, 2021)
Currently, various forms of employment are implemented in the labour markets. In Poland, non-standard forms are used to a relatively high extent. Based on the research covering a representative sample of 1,000 working Poles, it was analysed whether and depending on what factors employees can choose the form of employment. The quantitative data collection technique was used, consisting in providing information based on an online questionnaire (CAWI technique). The research findings showed that women, more often than men, work based on involuntary non-standard forms of employment. It was statistically confirmed that the share of involuntary forms of employment increases with age, thus the youngest employees declared the greatest freedom of choice. It was shown that large organizations, the companies with 100% foreign capital as well as public sector organizations most frequently impose the form of employment on their employees. The industry in which a given enterprise operates is also important. The lower possibility of choosing the form of employment in the groups disadvantaged on the labour market was assessed negatively. The assessment of organizations highlighted, however, that the limited choice of forms of employment may be related to a greater tendency in large, bureaucratic organizations to apply the solutions which do not raise legal doubts.
Keywords: non-standard forms of employment; work flexibility; involuntary forms of employment; labour market; gender; cohorts.